THE IMPORTANCE OF CULTURAL AWARENESS IN LANGUAGE TEACHING - Muxammadiyev Sherzod Obidjon o‘g‘li (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper examines the importance of cultural awareness in language teaching. It highlights how integrating culture improves communication, motivation, and intercultural competence, helping learners use language effectively in real-life situations.